Enhancing Air Travel Analysis: Forecasting Domestic Flight Activities in Indonesia based on Aircraft Types using MLP - Utari, Dina Tri; Sumarna, Zahra Maharani Putri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The COVID-19 pandemic has succeeded in bringing down various industrial sectors, including the aviation industry. This pandemic impacted the depletion of the operational fleet. In 2022, the number of domestic aircraft ready for operation was only around 55%–60% compared to 2019. However, with all its limitations, the aviation industry must develop the best strategy to revive in this post-pandemic era. One of the strategies undertaken is selecting the most efficient and economical aircraft type to cut costs amid market uncertainty due to this pandemic. In this regard, research was carried out to predict when aviation activity in Indonesia would reach regular in January 2020 and the forecast for the dominance of aircraft types in domestic flight. Multilayer Perceptrons (MLP) show that domestic flight activities in Indonesia will reach the standard point in March 2024. From the forecast result, the error rate using MAPE is 0.52%. The aircraft that dominates Indonesia’s domestic flight activities during 2020–2022 is the Airbus 320 type. Meanwhile, for the next two years—2023 & 2024—it is predicted that the Airbus 320 type will continue to dominate the flights.